The effects of arousal reappraisal on stress responses, performance and attention - Sammy, N.; Anstiss, P. A.; Moore, L.J.; Freeman, P.; Wilson, M. R.; Vine, S. J. (Anxiety, Stress and Coping, 2017)
Background and Objectives: This study examined the effects of arousal reappraisal on cardiovascular responses, demand and resource evaluations, self-confidence, performance and attention under pressurized conditions. A recent study by Moore et al. [2015. Reappraising threat: How to optimize performance under pressure. Journal of Sport and Exercise Psychology, 37(3), 339-343. doi:10.1123/jsep.2014-0186] suggested that arousal reappraisal is beneficial to the promotion of challenge states and leads to improvements in single-trial performance. This study aimed to further the work of Moore and colleagues (2015) by examining the effects of arousal reappraisal on cardiovascular responses, demand and resource evaluations, self-confidence, performance and attention in a multi-trial pressurized performance situation.